Lisinopril effects on platelet activity in patients with arterial hypertension and impaired glucose tolerance - I. N. Medvedev; O. V. Gamolina (Российский кардиологический журнал)
The study investigated ACE inhibitor lisinopril (Diroton, Gedeon Richter, Hungary) effects on platelet aggregation in patients with arterial hypertension (AH) and impaired glucose tolerance (IGT). Lisinopril was administered to 35 patients for 12 weeks. Dynamics of lipid profile, plasma and platelet lipid peroxidation, blood and platelet antioxidant potential, and platelet aggregation were assessed. Statistical methods included t-test. Lisinopril therapy in AH and IGT patients improved platelet aggregation and reduced peroxidation syndrome.